Role of Sorafenib in Patients With Recurrent Hepatocellular Carcinoma After Liver Transplantation. (December 2016) - de'Angelis, Nicola; Landi, Filippo; Nencioni, Marco; Palen, Anais; Lahat, Eylon; Salloum, Chady; Compagnon, Philippe; Lim, Chetana; Costentin, Charlotte; Calderaro, Julien; Luciani, Alain; Feray, Cyrille; et al.
Context: The management of hepatocellular carcinoma (HCC) recurrence after liver transplantation (LT) is challenging, especially if it is not treatable by surgery or embolization. Objectives: The present study aims to compare the survival rates of liver transplanted patients receiving sorafenib or best supportive care (BSC) for HCC recurrence not amenable to curative intent treatments. Design: This is a retrospective comparative study on a prospectively maintained database. Participants: Liver transplanted patients with untreatable HCC recurrence receiving BSC (n = 18) until 2007 or sorafenib (n = 15) thereafter were compared. Results: No group difference was observed for demographic characteristics at the time of transplantation and at the time of HCC recurrence. On the explant pathology of the native liver, 81.2% patients were classified within the Milan criteria, and 53.1% presented with microvascular invasion. Hepatocellular carcinoma recurrence was diagnosed 17.8 months (standard deviation: 14.5) after LT, with 17 (53.1%) patients presenting with early recurrence (≤12 months). The 1-year survival from untreatable progression of HCC recurrence was 23.9% for the BSC and 60% for the sorafenib group ( P = .002). The type of treatment (sorafenib vs BSC) was the sole independent predictor of survival (hazard ratio: 2.98; 95% confidence interval: 1.09-8.1; P = .033). In the sorafenib group, 8 (53.3%) patients required dose reduction, and 2 (13.3%) patients discontinued the treatment due to intolerable side effects. Conclusion: Sorafenib improves survival and is superior to the BSC in cases of untreatable posttransplant hepatocellular carcinoma recurrence.